The Maternal Serological Response to Intrauterine Ureaplasma sp. Infection and Prediction of Risk of Pre-Term Birth - Ireland, Demelza J.; Keelan, Jeffrey A. (Frontiers in Immunology, 2014)
Preterm birth (PTB) associated with intrauterine infection and inflammation (IUI) is the major cause of early PTB less than 32 weeks gestation. Ureaplasma sp. are common commensals of the urogenital tract in pregnancy and are the most commonly identified microorganism in amniotic fluid of preterm pregnancies. While we have an understanding of the causal relationship between intraamniotic infection, inflammation and PTB, we are still unable to explain why vaginal Ureaplasma colonization is tolerated in some women but causes PTB in others. It is now known that placental tissues are frequently colonized by bacteria even in apparently healthy pregnancies delivered at term; usually this occurs in the absence of a significant local inflammatory response. It appears, therefore, that the site, nature and magnitude of the immune response to infiltrating microorganisms is key in determining pregnancy outcome. Some evidence exists that the maternal serological response to Ureaplasma sp. colonization may be predictive of adverse pregnancy outcome, although issues such as the importance of virulence factors (serovars) and the timing, magnitude and functional consequences of the immune response await clarification. This mini-review discusses the evidence linking the maternal immune response to risk of PTB and the potential applications of maternal serological analysis for predicting obstetric outcome.